Analysis of weld defects in similar and dissimilar resistance seam welding of aluminium, zinc and galvanised steel. (26th May 2015) - Mira-Aguiar, T.; Galvão, I.; Leitão, C.; Rodrigues, D. M.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present investigation, a microstructural characterisation of welds performed by resistance seam welding was carried out, with special focus on weld defect analysis. In order to perform a comparative weldability analysis, the welds were performed using similar welding procedures. Similar welds in aluminium (5754-H22) and zinc (Zintek) alloys, as well as dissimilar welds between galvanised steel and zinc, were studied. The defective aluminium welds were found to be characterised by important grain growth inside an inhomogeneous nugget and by the presence of important voids and cracks. The zinc welds showed a well defined nugget, but with porosities and some cracks. In the dissimilar steel–zinc welds, important macroscopic defects were observed. Microstructural analysis evidenced the occurrence of melting at the zinc side of the welds; meanwhile, no microstructural modifications could be observed for the steel side. Defect formation, as well as weld morphologies, was related to the variation in welding parameters.